Child Mental Health Education After The Covid-19 Pandemic - Dita Kurnia Hati; Bayu Eko Broto; Azidin Harahap (International Journal Of Community Service, 2022)
The Covid-19 pandemic is a disease outbreak that has spread not only in Indonesia but throughout the world. This virus not only affects our physical health but also affects our mental health. Even though the government has now declared Indonesia to be free of masks, it cannot be denied that the coronavirus is still among us. For this reason, it is important to maintain good physical and mental health. During the pandemic, many people feel the consequences, especially children who still don't understand what is going on. In addition, the lack of awareness of us or our parents about mental health is a problem that must be faced. Mental health is a condition when our mind is peaceful and calm, so we can live a good life too, while children's mental health is related to how children face the challenges that exist in their lives. Community Service (PKM) "children's mental health education counseling after the covid-19 pandemic" which was held at the Miftahul Ilmi Kindergarten/RA school was carried out as a form of concern for how important mental health is to be maintained even after pandemic period has passed. The implementation of Community Service (PKM) is carried out on a scale through two stages, namely: the observation stage and the activity implementation stage. In the implementation stage, it is carried out through the lecture/discussion method of question and answer. The participants provided material on what mental health is, recognizing mental health problems in children, the effects of the COVID-19 pandemic on children's mental health, and the importance of maintaining mental health as well as tips for maintaining mental health in children. The result of this Community Service (PKM) activity is that previously there were still many parents who did not understand that not only physical health must be maintained but children's mental health also has a very large role in the body of children's development in the future to live their lives.